2018
DOI: 10.1158/0008-5472.can-18-0650
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Glioma Cells Exhibit Stem Cell-like Properties

Abstract: Circulating tumor cells (CTC) are known to be present in the blood of glioblastoma (GBM) patients. Here we report that GBM-derived CTC possess a cancer stem cell (CSC)-like phenotype and contribute to local tumorigenesis and recurrence by the process of self-seeding. Genetic probes showed that mouse GBM-derived CTC exhibited Sox2/ETn transcriptional activation and expressed glioma CSC markers, consistent with robust expression of stemness-associated genes including SOX2, OCT4, and NANOG in human GBM patient-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 37 publications
(38 reference statements)
2
69
0
Order By: Relevance
“…88 The authors identified positive CTCs as cells that met at least one of the following criteria: they were at least 9 µm in size, and were negative for CD45 staining; they were positive for EGFR, Ki67 or the microtubule-associated protein EB1, as well as being CD45 negative. Liu et al 89 , also in 2018, isolated CTCs from GBM patients as previously described 79 and characterised their stemness by immunohistochemistry by using Olig2 and CD133. 89 A mouse model was used to show the capacity of CTCs to reseed the primary tumour site when injected intravenously.…”
Section: Ctcs In Glioblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…88 The authors identified positive CTCs as cells that met at least one of the following criteria: they were at least 9 µm in size, and were negative for CD45 staining; they were positive for EGFR, Ki67 or the microtubule-associated protein EB1, as well as being CD45 negative. Liu et al 89 , also in 2018, isolated CTCs from GBM patients as previously described 79 and characterised their stemness by immunohistochemistry by using Olig2 and CD133. 89 A mouse model was used to show the capacity of CTCs to reseed the primary tumour site when injected intravenously.…”
Section: Ctcs In Glioblastomamentioning
confidence: 99%
“…Liu et al 89 , also in 2018, isolated CTCs from GBM patients as previously described 79 and characterised their stemness by immunohistochemistry by using Olig2 and CD133. 89 A mouse model was used to show the capacity of CTCs to reseed the primary tumour site when injected intravenously. Also, by using cell viability and apoptosis assays, the authors analysed the resistance of CTCs to radiotherapy and chemotherapy with TMZ and concluded that CTCs are more resistant to treatments and to stress induced in the circulation than other tumour cells.…”
Section: Ctcs In Glioblastomamentioning
confidence: 99%
“…Resection, chemo-embolization, surgery ablation and radiotherapy are the most commonly curative treatments in the clinic [22][23][24]. However, the postoperative 2-year recurrence rate remains high and the long-term survival prognosis of patients is still poor [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma-derived CTCs presented EGFR amplification, which is linked with the presence of EGFRvIII and aggressiveness of the disease [74]. Cultured CTCs were shown to express the sex-determining region Y-box 2 (SOX2), octamer-binding transcription factor 4 (OCT4), and homeobox protein NANOG, which are glioblastoma stem cell markers [76], and also markers associated with very aggressive mesenchymal subtype, serpin family E member 1 (SERPINE1), vimentin (VIM), transforming growth factor-beta 1 (TGFB1), and transforming growth factor-beta (TGF-β) receptor type 2 (TGFBR2) [7]. They also contribute to resistance to treatment with temozolomide and radiotherapy [76].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%